Design of the North Carolina Prostate Cancer Comparative Effectiveness and Survivorship Study (NC ProCESS). (January 2015) - Chen, Ronald C; Carpenter, William R; Kim, Mimi; Hendrix, Laura H; Agans, Robert P; Meyer, Anne-Marie; Hoffmeyer, Anna; Reeve, Bryce B; Nielsen, Matthew E; Usinger, Deborah S; Strigo, Tara S; Jackman, Anne M; et al.
The North Carolina Prostate Cancer Comparative Effectiveness & Survivorship Study (NC ProCESS) was designed in collaboration with stakeholders to compare the effectiveness of different treatment options for localized prostate cancer. Using the Rapid Case Ascertainment system of the North Carolina Central Cancer Registry, 1, 419 patients (57% of eligible) with newly-diagnosed localized prostate cancer were enrolled from January 2011 to June 2013, on average 5 weeks after diagnosis. All participants were enrolled prior to treatment and this population-based cohort is sociodemographically diverse. Prospective follow-up continues to collect data on treatments received, disease control, survival and patient-reported outcomes. This study highlights several important considerations regarding stakeholder involvement, study design and generalizability regarding comparative effectiveness research in prostate cancer.